Lexical Density and Readibility of Joe Biden’s Victory Speech - Sonya Sibagariang (Mimbar Ilmu, 2023)
This research focuses on the readability and lexical density of Joseph Robinette Biden Jr.'s speech, more commonly referred to as Joe Biden's victory speech. This research aims to analyze the verbal density and readability of Joe Biden's victory speech. This research uses a mixed quantitative and qualitative research design. The primary data source for this research is Joe Biden's speech to win the election. The data collection instrument uses a questionnaire. Data analysis techniques are qualitative and quantitative descriptive analysis. The research results were 852 content words and 990 grammar words. This text contains a lexical density of 46.2, which places it in the high verbal density classification. Beverly's theory, q (1988), states that the readability score is 64.23, which means that standard, there are 142 sentences, 1842 words, and 2833 syllables. The influence of his speech on lexical density and readability shows that he used words that listeners easily understood because they expressed a lot of gratitude and happiness. His speech also reflected Biden's character, who loves to praise, is full of hope, is brave, and is not fanatical. Hence, the American people admired people, which led him to become America's leader.